If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 60 = 35 Reorder the terms: 60 + X = 35 Solving 60 + X = 35 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + X = 35 + -60 Combine like terms: 60 + -60 = 0 0 + X = 35 + -60 X = 35 + -60 Combine like terms: 35 + -60 = -25 X = -25 Simplifying X = -25
| (2+v)(2v+3)=0 | | 3x(12x-5)-6x(6x-5)=0 | | 4x^3-9x^2+7x=2.5 | | 6x-17=2x+15 | | (√48)^(1/2) | | y=5-2n | | 8x-5y=2132 | | 2x+3(2x-5)=6 | | 13+3x=-91-10x | | 2x+15=4x+11 | | 34m-5-1/2m=1 | | 24-4x=9-7x | | X-(7x-8)= | | 8x-y=32 | | 5/6=1/x | | a+3b-4c=0 | | y=zx-2x+5 | | 18-x=x-2 | | 6y+2x=16 | | 5ex=15.76 | | (a+2b)(a^2-2ab+4b^2)= | | (m+1)(m^2-m+1)= | | (2a-b)(2a-b)= | | x+5*7=133 | | cos(x)=0.333333 | | sin(x)=0.33 | | -4x^2y^2= | | 12(3n-5)= | | 8x15sequre15/8x5sequre | | X^2-(p-2)x+2p+1=0 | | X+(5y)=65 | | 3x+10=28-3x |